PENGGUNAAN TEORI BELAJAR SIBERNETIKA SEBAGAI METODE PEMBELAJARAN BAHASA INDONESIA TINGKAT SEKOLAH DASAR - Nurfitria; Reni Fitri Sopiah; Rismayani; Tsani Rubayyi Sunja (Jurnal Cakrawala Ilmiah, 2024)
The purpose of writing this article is to fulfill the assignment for the Final Semester Examination for the Indonesian Language corse. Apart from that, another aim of writing this article is to be able to find out Indonesian language learning methods using learning media combined with learning methods based on a learning curriculum that is in accordance with the government based on cybernetic learning theory. In the educational context, cybernetic learning is often synonymous with feedback. This feedback from students allows teachers to find out what students' difficulties are in understanding the material and whether the material presented has been understood or not. To produce efficient learning, you don't just need to use one method, but need several methods. The learning methods applied in the classroom must be in accordance with the material and the teacher's disposition so that it will produce students who are creative, productive and have good and correct knowledge. According to Anggit Sri, et al (2013) revealed that a process of interaction between students and learning resources in a learning environment is an understanding of the learning process. In order for the process of acquiring science and knowledge, mastering skills, habits, and forming attitudes and beliefs in students, educators provide assistance in the form of learning. In other words, the process of helping students to learn well is called learning. Thus, this article was written in the hope that it can fulfill the Mid-Semester Exam assignment for the Indonesian language course and become a reference for every reader to be able to develop their abilities in developing a learning process based on cybernetic learning theory.